ANALISIS TITIK PULANG POKOK USAHA BAWANG GORENG PADA INDUSTRI ACRAN SIGI DI DESA LOLU KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Haeruddin, Husnawati Haeruddin (AGROTEKBIS, 2016)
This study aimed to determine the break-even point of fried shallot business at Acran Sigi Industry in Lolu Village, Sigi Biromaru District, Sigi Regency. This study was conducted in Acran Sigi Industry in March-April 2016. The types of data used were primary and secondary data. The respondents of this study comprised two people, namely the owner of Acran Sigi Industry and an unfixed worker of Acran Sigi Industry. The results showed that the break-even point for the 100 g Original packaging was achieved at the production volume of 18 (eighteen) packagings, so that income obtained during the break-even point was of Rp 450,000. The break-even point for the 100 g Spicy packaging was achieved at the production volume of 15 (fifteen) packagings, so that income obtained during the break-even point was of Rp 405,000. The break-even point for the 200 g Original packaging was achieved at the production volume of 7 (seven) packagings, so that income obtained during the break-even point was of Rp 350,000. The break-even point for the 200 g Spicy packaging was achieved at the production volume of 6 (six) packagings, so that income obtained during the break-even point was of Rp 324,000. The results showed that Acran Sigi Industry had reached the favorable or profit area because production exceeded the break-even point.